Disability and poverty in Sri Lanka: a household level analysis - Kumara, P. H. T.; Gunewardena, D. N. B. (National Science Foundation: Colombo, 2017)
Sri Lanka has recorded a significant reduction in poverty in recent times. Yet, as in many other developing countries, little or nothing is known about poverty levels and reduction of poverty among the disabled or their households. The disabled and their families encounter different hardships than the typical deprivations of the poor. The recent literature questions the ability of the monetary approach in measuring poverty in general and especially among different groups like the disabled. Therefore, this study estimates both monetary and multidimensional poverty among the households with disabled persons, using the Household Income and Expenditure Survey data of 2006/07 and 2009/10. The study found that monetary and multidimensional poverty among households with disabled persons is higher than among other households. Even though multidimensional poverty is relatively low in Sri Lanka, the difference in multidimensional poverty levels between households with and without the disabled is high. Importantly, contributions from the three dimensions considered in this research to the incidence of poverty is almost equal, suggesting that further reduction of poverty in Sri Lanka requires improvements in all three dimensions - health, education and living standards- among poor households, with and without disabled persons.
Keywords: Poverty; Disability; Multidimensional poverty; Alkire-Foster method; Sri Lanka.